Identification of UBE2I as a Novel Biomarker in ccRCC Based on a Large-Scale CRISPR-Cas9 Screening Database and Immunohistochemistry - Li, Feng; Lai, Li; You, Zhijie; Cheng, Hui; Guo, Guodong; Tang, Chenchen; Xu, Luyun; Liu, Hongxia; Zhong, Wenting; Lin, Youyu; Wang, Qingshui; Lin, Yao; et al. (Frontiers in Molecular Biosciences, 2022)
Background: The Genome-wide CRISPR-cas9 dropout screening has emerged as an outstanding approach for characterization of driver genes of tumor growth. The present study aims to investigate core genes related to ccRCC cells viability by analyzing the CRISPR-cas9 screening database DepMap, which may provide a novel target in ccRCC therapy. Methods: Candidate genes related to ccRCC cells viability by CRISPR-cas9 screening from DepMap and genes differentially expressed between ccRCC tissues and normal tissues from TCGA were overlapped. Weighted correlation network analysis (WGCNA), pathway enrichment analysis, and protein-protein interaction (PPI) network analysis were applied for the overlapped genes. The LASSO regression was used to construct a signature to predict the overall survival (OS) of ccRCC patients and validated in ICGC and E-MTAB-1980 database. Core protein expression was determined using immunohistochemistry in 40 cases of ccRCC patients. Results: A total of 485 essential genes in DepMap database and overlapped with differentially expressed genes (DEGs) in the TCGA database, which were enriched in the cell cycle pathway. A total of 4 genes, including UBE2I, NCAPG, NUP93, and TOP2A were included in the gene signature based on LASSO regression. The High-risk score of ccRCC patients showed worse OS compared with These low-risk patients in the ICGC and E-MTAB-1980 validation cohort. UBE2I was screened out as a key gene. The immunohistochemistry indicated UBE2I protein was highly expressed in ccRCC tissues and a high-level nuclear translocation of UBE2I occurs in ccRCC. Based on the area under curve (AUC) values, nuclear UBE2I had the best diagnostic power (AUC=1). Conclusion: UBE2I, identified by CRISPR-cas9 screening, was a core gene-regulating ccRCC cells viability, which accumulated in the nucleus and acted as a potential novel promising diagnostic biomarker for ccRCC patients. Blocking the nuclear translocation of UBE2I may have potential therapeutic value with ccRCC patients.